2021
DOI: 10.54203/scil.2021.wvj23
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on Dog Bite Associated Rabies in Human and the Use of Post-exposure Prophylaxis in Nepal during 2008 to 2017

Abstract: A 10-year (2008-2017) retrospective canine-mediated human rabies epidemiology was studied to assess the burden of rabies in Nepal. To this end, the number of dog bites, the use of post-exposure prophylaxis (PEP), and human death records from 2008 to 2017 were retrieved from Sukraraj Tropical Hospital, Kathmandu, Nepal. The findings revealed that the number of human rabies occurrences was consistent with minor fluctuations throughout the study period. There were 252,297 dog bite cases in humans recorded between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The biting prevalence in Uruguay is lower than that reported in other countries from North America (Daigle et al., 2022 ; Overall & Love, 2001 ; Quirk, 2012 ) and from Oceania (Mair et al., 2019 ). Studies from Asia have variably reported higher (Abedi et al., 2019 ; Amiri et al., 2020 ; Babazadeh et al., 2016 ; Gongal & Wright, 2011 ) and slightly lower prevalence (Masiira et al., 2018 ; Pal et al., 2021 ). Similarly, the frequencies reported in European countries have been both higher (Westgarth et al., 2018 ) and slightly lower (Rosado et al., 2009 ) than found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The biting prevalence in Uruguay is lower than that reported in other countries from North America (Daigle et al., 2022 ; Overall & Love, 2001 ; Quirk, 2012 ) and from Oceania (Mair et al., 2019 ). Studies from Asia have variably reported higher (Abedi et al., 2019 ; Amiri et al., 2020 ; Babazadeh et al., 2016 ; Gongal & Wright, 2011 ) and slightly lower prevalence (Masiira et al., 2018 ; Pal et al., 2021 ). Similarly, the frequencies reported in European countries have been both higher (Westgarth et al., 2018 ) and slightly lower (Rosado et al., 2009 ) than found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, most of these bites were reported from urban areas, where the stray dog population is higher than the rural areas. 9 Regarding circumstances of animal bite, most were unprovoked. Unprovoked cases were as high as 81 to 87%.…”
Section: Discussionmentioning
confidence: 99%
“…2 Rabies has been endemic in Nepal with an underestimated annual death of 100 per year. 9,10 In Nepal, the transmission of rabies is from jackals to humans through stray dogs as the mediator. 10 The fenceless forests allowing contiguity of wild and pet animals and the free trade and movement of humans and animals across unbarred border with India has facilitated the transmission of infectious diseases.…”
Section: Clinico-epidemiological Study On Animal Bitementioning
confidence: 99%
See 1 more Smart Citation